Optimalisasi Layanan Perpustakaan di Era New Normal - Ulfah Rulli Hastuti (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2020)
Government policy in implementing the New Normal Era is a hope for people to rise from adversity in facing the Covid-19 pandemic. The enthusiasm and hope in welcoming the new life order provides an opportunity for the community to start carrying out activities that were previously restricted or stopped. The application of new normal is welcomed with a positive attitude in various sectors. In the library education sector welcomed positively with the new order of life that began to be applied gradually. How is the preparation done by the library to open services for users in this New Normal Era? The normal concept in library services must be really prepared, both in terms of human resources and collections. Three important things that must be considered to prepare library services are 1. Services must prioritize the health of librarians and users 2. Design services and facilities in the library 3. Make policy access to the library.